PENGARUH MEDIA APLIKASI PAKET TRACER MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP MOTIVASI DAN HASIL BELAJAR MATA PELAJARAN ADMNISTRASI INFRASTRUKTUR JARINGAN SISWA KELAS XI TKJ DI SMKN 2 BANGKALAN - Albab, Ulil; Purnamasari, Hetty; Isman, Soubar (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
One of the formal educational institutions is SMK Negeri 2 Bangkalan, which has a field of expertise in Computer Network Engineering, where graduates are expected to be able to compete in the business world, especially in the field of Computer Network Engineering. One of the productive subjects that support the achievement of skilled and creative quality graduates is Network Infrastructure Administration. In this subject, students are expected to be able to apply and practice their knowledge in the field of Computer Network Engineering. For this reason, students must really master network design and modeling, one of which is mastering the subject of Network Infrastructure Administration. The approach used in this study is a quantitative approach with experimental techniques on a population and research sample of 54 students. research data collection using questionnaires and tests that have gone through the stages of testing the validity and reliability. Analysis of research data using statistical methods with the formula t-test one sample and multiple correlations. Based on this analysis, the conclusions of the study are described, among others: 1) the learning motivation of Class XI TKJ students at SMKN 2 Bangkalan is quite good, 2) the implementation of problem based learning learning models in Class XI TKJ at SMKN 2 Bangkalan is quite good, 3) Utilization of Package Application Media Tracer in Class XI TKJ at SMKN 2 Bangkalan is quite good, 4) there is a significant influence between the utilization of the Tracer Package Application Media through the Problem Based Learning Learning Model and learning motivation on the learning outcomes of Class XI TKJ students at SMKN 2 Bangkalan